The first experience of laser scalpel «LS-0,97» application at endoscopic ablation of rectal polyps - V. S. Rubtsov; Yu. V. Chalyk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To discuss potential of highenergy 970 nm laser radiation for radical ablation of sessile polyps of the rectum.Material and methods. Laser scalpel «LS-0,97- IRE-Poljus» (Russia) was used as a source of highenergy laser radiation. Polyp erasion was implemented by «Olympus CF-EI» colonoscope (Japan). The contact laser photocoagulation was applied in continuous mode using quartz monothread 600 microns in diameter. Totally 16 polyps of the rectum at 11 patients over 45 years old were removed by laser ablation.Results. Radical erasion of 16 sessile rectal polyps 0,4 to 1,0 cm in size was carried out. No complications during laser photocoagulation procedure and in postoperative period were observed. At control endoscopy 6 to 12 months after erasion no relapse of polyps was revealed.Conclusions. The procedure of laser photocoagulation by 970 nm radiation allows to remove sessile polyps of rectum of the small size in out-patient conditions. Special investigation is required for evaluation of safety of this procedure for ablation of flat polyps of the colon.